Nghị quyết về việc xác nhận đủ tư cách đại biểu Quốc hội khóa XV (Số: 782/NQ- HĐBCQG) - Hội đồng bầu cử quốc gia (2021)
Toàn văn Nghị quyết về việc xác nhận đủ tư cách đại biểu Quốc hội khóa XV (Số: 782/NQ- HĐBCQG)